Evaluation and response of dental pulp stem cells following pulp capping procedure using calcium hydroxide cement and gic or restorative procedure using gic in primary molars - Noor, Siti Noor Fazliah Mohd; Kannan, TP (2008)
The biological examination of pulp injury, repair events and the response of dental pulp stem cells to dental restorative materials is of paramount importance for understanding the post operative development and the use of these repair activities to accomplish restorative treatment.The structure of the tooth is almost always exposed to different dental materials and the deciduous teeth are known to be a rich source of stem cells. Therefore, it is important to evaluate the response of dental pulp stem cells to the commonly used dental materials in pediatric dentistry such as Glass Ionomer Cement (GIC) and Calcium hydroxide Ca(OH)2 lining cement. The aims of this study were to confirm the presence of stem cells in deciduous extracted teeth by immunocytochemistry, and evaluate the stem cells proliferative activity and their response by comparing the Tertiary Dentin Thickness (TDT) formation following restorative procedures on the teeth. Healthy pediatric dental patients aged between 9 to 11 years old with caries teeth on primary molars without pulpal exposure who attended the pediatric dental clinic for dental treatment in School of Dental Sciences, Health Campus, Universiti Sains Malaysia, were selected.The teeth were divided into two groups: for Group 1 the teeth were filled with GIC(Fuji IXGP capsule, GC, Japan) alone and in Group 2, the teeth were lined with Ca(OH)2 cement (Dycal ®, Dentsply, Germany) and filled with GIC (Fuji IXGP capsule, GC, Japan).The teeth were reviewed for up to 6 months before being extracted according to the selected criteria and under standardized normal procedures. The presence of stem cells in deciduous teeth was confirmed by immunocytochemistry using surface antigenic markers CD 1 OS and CD 166.Colocimetric proliferation reagent alamarBlue™ was used to evaluate the proliferative activity for Group 1 and Group 2. The dental pulp stem cells response following restorative procedures was evaluated using Haematoxyline and Eosin (H&E) staining for histological section under a microscope using image pro software (Media cypemetics. Inc., USA). Stem cells from human extracted deciduous teeth were found positive for CD 105 and CD 166. The proliferative activity for both Group 1 and Group 2 showed slight difference, but it was not statistically significant.However, the TDT areas in Group 2 were significantly more than Group 1. The pulp of deciduous teeth contains stem cell population and following pulp capping procedure using Ca(OHh cement (Dycal®, Dentsply, Germany) and GIC (Fuji IXGP capsule, GC, Japan), responded well and maintained their proliferative activity. However, these materials create different response of SHLD tertiary dentin appeared to be more under restorations lined with Ca(OHh. Thus Ca(OHh cement has high credibility to be used in deep cavities for pulp protection.